2020
DOI: 10.1016/j.msard.2020.102415
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cervical stenosis on multiple sclerosis lesion distribution in the spinal cord

Abstract: To determine whether demyelinating lesions attributable to multiple sclerosis (MS) occur more commonly in regions of pre-existing cervical stenosis (CS).Design/Methods: One hundred comorbid MS/CS patients and 100 MS-only controls were identified via ICD codes and radiology reports from a retrospective chart review of the records of the University of Pennsylvania Hospital System (UPHS) from January 1 st , 2009 to December 31 st , 2018. For each patient, axial and sagittal T2 sequences of cervical MRI scans were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…A recently published study also suggested an association between MS lesions and at least moderate cervical stenosis. 11 However, our study did not find any association between cervical discopathy and MS lesions in the corresponding cervical segment. The discordance between the results of the studies could be attributed to differences in genetic and environmental factors between study populations.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…A recently published study also suggested an association between MS lesions and at least moderate cervical stenosis. 11 However, our study did not find any association between cervical discopathy and MS lesions in the corresponding cervical segment. The discordance between the results of the studies could be attributed to differences in genetic and environmental factors between study populations.…”
Section: Discussioncontrasting
confidence: 80%
“…10 A more recent study suggested a similar association between MS lesions and at least moderate cervical stenosis. 11 In our study, we reviewed the clinical data and magnetic resonance imaging (MRI) scans of MS patients with discopathy seen at our MS clinic in 2018, and examined the possible association between them.…”
Section: Introductionmentioning
confidence: 99%
“…At autopsy, Brain and Wilkinson [24] had noted that cord demyelination was most extensive at compression sites. Lesions typical of MS were more likely to occur at levels of existing cervical spondylosis, versus levels without, in PwMS [36]. The pathophysiological basis for such an interaction could include bystander activation of local inflammatory responses in either cord parenchyma or surrounding musculoskeletal structures, as well as compressive ischaemia of the cord.…”
Section: Discussionmentioning
confidence: 99%
“…in PwMS [36]. The pathophysiological basis for such an interaction could include bystander activation of local inflammatory responses in either cord parenchyma or surrounding musculoskeletal structures, as well as compressive ischaemia of the cord.…”
Section: Re Sults Main Study: Objective Assessmentmentioning
confidence: 99%
“…Regarding intramedullary spinal neurosarcoidosis occurring as isolated CNS involvement only at sites of spinal canal stenosis, it has long been postulated that other inflammatory lesions, specifically MS plaques, tend to occur at sites of cord trauma and degenerative stenosis, with close anatomic correspondence between mechanical stresses on the cord by spondylosis and spinal cord MS plaques. 22,23 The trauma could result in loss of blood-cord barrier impermeability, which could allow the entrance of the antigen responsible for sarcoidosis into the cord as well as the entrance of T lymphocytes to set off the inflammatory cascade. As stated by Hickey, 24 "any mechanism that physically destroys the components of the blood cord barrier will render the CNS open to the cellular and molecular constituents of the blood.…”
Section: Intramedullary Spinal Neurosarcoidosis At the Level Of Cervi...mentioning
confidence: 99%